Conocimiento y actitud frente a exposición solar del personal de salud en Atención Primaria, comuna Recoleta, Santiago, Chile - Contreras N., Andrés; Zemelman D., Viviana; Zamudio M., Andrea (Revista Hospital Clínico Universidad de Chile, 2016)
Introduction: Skin cancer rates have increased worldwide despite the current prevention measures. It’s crucial to evaluate people’s knowledge, attitudes, and behaviour regarding sun exposure. Objective: To assess the knowledge and attitudes regarding sun exposure in the workers from primary health care. Method: 223 workers from three Family Care Centres(CESFAM) and from one Primary Emergency Service (SAPU) in the district of Recoleta were surveyed between the months of October and November 2015. Fisher’s exact test and Chi square test were used for statistic analysis. The survey included questions about demographic variables, knowledge of the association between sun radiation/skin cancer and attitudes towards sun protection. Results: the sample consists of 74 men and 149 women, with a mean age of 37 years ±SD 7.9. Phototype III was the most common (41.3%). The majority of the surveyed declared to be aware of the association between sun exposure and skin cancer (93.3%). As photoprotecting measures, sunscreens (87.4%) and seeking shade (71.3%) were the most frequently measures used. Regarding sunburns, 91.9% declared to have at least one during their lifetime, 21.5% occurring during the previous summer. As to the use of sunscreen, 42.1% referred only using while at the pool / beach and 12.6% declared not to use it at all. As for health promotion, 29.1% declared they never recommend the use of sun protection measures in their working practice. Discussion: Although there is adequate knowledge regarding the effects of sun exposure, it doesn’t always reflect on favourable attitudes and photoprotecting measures. There was a significantly greater amount of females with adequate knowledge and use of sun protection measures. This study is one of the first to assess photoprotection behaviour in health care workers.